Pre-literary classical influences on two early Germanic heroic legends - Parkhouse, J (2020)
This thesis argues for the influence of Graeco-Roman mythological ideas on two Germanic legendary traditions in the context of interactions between the Germanic-speaking peoples and the Roman Empire in Late Antiquity. Documentary and archaeological evidence testifies to diverse contacts between the Roman world and the Germanic-speaking peoples, intensifying from the third century CE. There are numerous indications of Roman cultural influence on the Germanic-speaking peoples during this period. Material evidence illustrates the conscious emulation of Romanitas amongst Germanic elites, and in particular evidence of the adaptation of Roman ritual and religious influences corroborates the case for the diffusion of mythological material. Legends concerning the revenge of the master smith Wayland and the destruction of the Burgundian kingdom by the Huns developed amongst Germanic-speaking groups during this period, and are preserved in variant forms in medieval texts from Scandinavia, Germany and England. A synthesis of these three branches of literary sources with iconographic material and the evidence of Latin historiography shows several features in both legends that were incorporated into the earliest strata of their pre-literary development. The elements in question are closely paralleled in the classical myths of Daedalus and Medea, and the wide circulation of these myths in the Roman world in Late Antiquity provides a plausible impetus for their accretion into nascent Germanic legendary traditions. The correspondences between the classical and Old Norse texts are additionally studied from an analogical perspective, considering the ways in which they can highlight underlying similarities and differences in the gender dynamics of the cultures that gave rise to the different literary corpora.